ONTOLOGICAL FOUNDATIONS OF MORAL CULTURE. Part I - Морозов, Андрій; Шаповалов, Владислав (Ukrainian Cultural Studies, 2023)
The relevance. Forgetting the problems of being, erasing the idea of being from the worldview of modern man, and focusing on individualistic and hedonistic practices leads to the narrowing of the personality‘s fullness, dehumanization of its moral and spiritual dimension, and alienation from one's essence. Philosophical reactualization of being and its metaphysical essential foundations will allow finding a reliable ontological foundation for a shaken by skepticism and nihilism moral culture, and for the human who lost his essence. Goal. The purpose of the article is to study the ontological foundations of moral culture. The tasks of the first part of the article are to investigate the ontological framework of moral culture, and the fundamental axes on which it is based; the tasks of the second part of the article are to analyze the moral concepts of freedom, conscience, dignity, and equality through the prism of the ontological framework. Methods. The article uses a historical-philosophical and comparative method, genealogy, and hermeneutic methods of interpretation. The results. Ethical relations unfold in the value-meaning space of moral culture between the Self and the Other. The transcendental condition for the possibility of moral culture is reality and its internal structure, the parameters of which are set by the ontological framework, namely by the poles of attraction of singular and multiple, sacred and profane, phenomenal (existential) and essential. It is shown that the Western metaphysical tradition managed to find a balance between the extremes of the single and multiple, while the Eastern tradition of Hinduism, on the one hand, and the anti-metaphysical trends of the 19th and 20th centuries, on the other hand, absolutized one or the other extreme. Conclusions. Moral culture cannot be built and substantiated in isolation from ontology, and therefore without addressing being as the sphere of the real. Both metaphysical and anti-metaphysical philosophical systems are based on ontological assumptions. Without being rooted in ontology, ethics risks losing reality and realness. The transcendental "yes" or "no" to being enables further forms of moral relations and principles that exist in culture.
Keywords: ethics; moral culture; Other; ontological frame; (non)metaphysical tradition; Aufheben; being as a sacred gift; transcendental "yes" and "no"